Brand equity and competitive advantage in alcoholic beverage products - Emenike O., Kalu; Moses, Agaba (Inderscience Enterprises Ltd, 2022)
In the face of growing competition in modern business environment as a result of globalisation and development in information and communication technology, firms are required to gain and sustain competitive advantage. This study therefore investigated the effect of brand awareness, brand association, brand loyalty, perceived quality, and other proprietary brand assets on competitive advantage in alcoholic beverage products and producers in Kabale District Uganda. The study employed descriptive and multiple regression analyses. The estimates from the multiple regression model indicated that brand equity has significant effect on competitive advantage among alcoholic beverages products and producers. This is evident in the statistical significance of the brand awareness, brand loyalty, and perceived quality variables at the 5% significant. We conclude therefore that brand equity has positive and significant predictive effect on competitive advantage. Hence, firms could enhance competitive advantage by paying attention to brand equity variables.